Multiple supernumerary teeth in the maxillary canine and mandibular premolar regions: a case in the postpermanent dentition - HIDEKAZU SASAKI, JUNKO FUNAO, HIDEKI MORINAGA, KAZUHIKO NAKANO, & TAKASHI OOSHIMA (IAPD and Blackwell, 2007)
A supernumerary tooth is defined as an extra tooth that develops in addition to the normal number found in dentition.